The Eurosceptical Reader
XV, 410 p.
Keywords: The Eurosceptical Reader is the authoritative guide to the compelling arguments against European integration. The book sets out to dispel the myth which has grown up over the past thirty years that Britain's Eurosceptics are backward-looking, nationalistic, even xenophobic 'Little Englanders'. In reality, as this collection of articles and speeches illustrates, the Eurosceptical case has been anything other than introverted and obsessed with the past. Eurosceptics have always looked to the wider world beyond Europe not to a nostalgic British isolation. Whether from within the two main parties or from academia and journalism, the Eurosceptical case has become both intellectually powerful and politically persuasive. The all-star cast provides contemporary analysis to supplement classic contributions from Hugh Gaitskell, Margaret Thatcher, Enoch Powell, Tony Benn and others.